Religious Persecution, Refugees, and Right of Asylum: The Case of The Church of Almighty God - Šorytė, Rosita (The journal of CESNUR, 2018)
International conventions and both United Nations and European Union guidelines establish general principles about religion-based refugee claims. They clarify that “religion” should be broadly interpreted, and that it is not necessary for the asylum seekers to prove that they have been individually persecuted. Membership in a persecuted group and a reasonable “fear of persecution” are enough. Proving that the asylum seeker is deeply conversant with the theology of the persecuted group is also not required. However, these general principles are rarely applied by states. The paper discussed the case of The Church of Almighty God, whose members are often denied refugee status in South Korea and Europe, based both on an incorrect interpretation of the international conventions and on inaccurate information about their church.